Genetic variability, correlation and path analysis in fenugreek (Trigonella foenum-graecum L.) - Kole, Ananya Banerjee, P C (Journal of Spices and Aromatic Crops, 2004)
Genetic variability was studied in a population of 22 genotypes of fenugreek (Trigonella foenum-graecum) at Sriniketan (West Bengal). Phenotypic and genotypic coefficients of variability were high for stem weight; moderate for plant height, branches plant-1, days to flowering, duration of flowering, shelling per cent and test weight; and low for pod length. High to moderate estimates of heritability coupled with moderate to high genetic advance were recorded for plant height, days to flowering, duration of flowering, shelling per cent and test weight indicating the predominance of additive gene action. Grain yield was positively correlated with branches plant-1 pods plant-1, pod length, seeds pod-1, pod weight, biological yield, shelling per cent and harvest index at both phenotypic and genotypic levels. Results of path analysis revealed that days to flowering, pods plant-1, pod length and seeds podol are the important characters determining seed yield in fenugreek.